Identification of patients eligible for discharge within 48 h of colorectal resection. Issue 5 (7th January 2020) - Grass, F; Hübner, M; Mathis, K L; Hahnloser, D; Dozois, E J; Kelley, S R; Demartines, N; Larson, D W
Abstract: Background: This study aimed to identify patients eligible for a 48-h stay after colorectal resection, to provide guidance for early discharge planning. Methods: A bi-institutional retrospective cohort study was undertaken of consecutive patients undergoing major elective colorectal resection for benign or malignant pathology within a comprehensive enhanced recovery pathway between 2011 and 2017. Overall and severe (Clavien–Dindo grade IIIb or above) postoperative complication and readmission rates were compared between patients who were discharged within 48 h and those who had hospital stay of 48 h or more. Multinominal logistic regression analysis was performed to ascertain significant factors associated with a short hospital stay (less than 48 h). Results: In total, 686 of 5122 patients (13·4 per cent) were discharged within 48 h. Independent factors favouring a short hospital stay were age below 60 years (odds ratio (OR) 1·34; P = 0·002), ASA grade less than III (OR 1·42; P = 0·003), restrictive fluid management (less than 3000 ml on day of surgery: OR 1·46; P < 0·001), duration of surgery less than 180 min (OR 1·89; P < 0·001), minimally invasive approach (OR 1·92; P < 0·001) and wound contamination grade below III (OR 4·50; P < 0·001), whereas cancer diagnosis (OR 0·55; P < 0·001) and malnutrition (BMI below 18 kg/m 2 : OR 0·42; P = 0·008) decreased the likelihood of early discharge. Patients with a 48-h stay had fewer overall (10·8 per cent versus 30·6 per cent in those with a longer stay; P < 0·001) and fewer severe (2·6 versus 10·2 per cent respectively; P < 0·001) complications, and a lower readmission rate (9·0 versus 11·8 per cent; P = 0·035). Conclusion: Early discharge of selected patients is safe and does not increase postoperative morbidity or readmission rates. In these patients, outpatient colorectal surgery should be feasible on a large scale with logistical optimization. Graphical Abstract: Early discharge within 48 h of colorectal resections is safe in selected patients and does not increase postoperative morbidity or readmission rates. In these patients, outpatient colorectal surgery should be feasible on a large scale with logistical optimization. Safe in some